CK2β Is a Gatekeeper of Focal Adhesions Regulating Cell Spreading - Filhol, Odile; Hesse, Anne-Marie; Bouin, Anne-Pascale; Albigès-Rizo, Corinne; Jeanneret, Florian; Battail, Christophe; Pflieger, Delphine; Cochet, Claude (Frontiers in Molecular Biosciences, 2022)
CK2 is an hetero-tetrameric serine/threonine protein kinase made up of two CK2α/α’ catalytic subunits and two CK2β regulatory subunits. The free CK2α subunit and the tetrameric holoenzyme have distinct substrate specificity profiles suggesting that the spatiotemporal organization of the individual CK2 subunits observed in living cells is crucial in the control of the many cellular processes that are governed by this pleiotropic kinase. Indeed, previous studies reported that unbalanced expression of CK2 subunits is sufficient to drive epithelial to mesenchymal transition (EMT), a process involved in cancer invasion and metastasis. Moreover, sub-stoichiometric expression of CK2β compared to CK2α in a subset of breast cancer tumors was correlated with the induction of EMT markers and increased epithelial cell plasticity in breast carcinoma progression. Phenotypic changes of epithelial cells are often associated with the activation of phosphotyrosine signaling. Herein, using phosphotyrosine enrichment coupled with affinity capture and proteomic analysis, we show that decreased expression of CK2β in MCF10A mammary epithelial cells triggers the phosphorylation of a number of proteins on tyrosine residues and promotes the striking activation of the FAK1-Src-PAX1 signaling pathway. Moreover, morphometric analyses also revealed that CK2β loss increases the number and the spatial distribution of focal adhesion signaling complexes that coordinate the adhesive and migratory processes. Together, our findings allow positioning CK2β as a gatekeeper for cell spreading by restraining the focal adhesion formation and invasion of mammary epithelial cells.